Localizing demand and supply of environmental services: interactions with property rights, collective action and the welfare of smallholders - Swallow, Brent M.; Meinzen-Dick, Ruth S.; van Noordwijk, Meine (2006)
This paper presents a conceptual framework that clarifies the inter-linkages between property rights, collective action, payment for environmental services, and the welfare of smallholder land users. The framework is centered on concerns of function and welfare effects of PES. The functional perspective clarifies the effects of collective action and property rights institutions on the supply of environmental services. The welfare perspective considers smallholders as one of several potential sources of supply,sometimes directly competing against large landowners and public sector providers.